Development of Student Worksheets Problem Solving Oriented to Train Metacognitive Skills Students Grade XI on Acid Base Materials - Dian Zulfatur Rizqiyah; Utiya Azizah (Universitas Pendidikan Mandalika, 2023)
This study aimed to describe the feasibility of student worksheets with problem solving oriented to train metacognitive skills on acid base material. The feasibility of student worksheets developed in terms of aspects, namely validity, practicality, and effectiveness. The type of this research used Borg and Gall Research and Development (R&D), and the design of this research used one group pretest-posttest design with the objects are 24 students on 11th grade in science 2 of SMAN 1 Dawarblandong. The results showed that the student worksheets were declared feasible of the validity, practicality, and effectiveness. The validity was measured by the content and construct validation sheets. The practicality was measured by the students’ responses and average observation of students’ activities. The effectiveness was measured by pretest-posttest of metacognitive skills, knowledge domain test, and supported by the metacognitive inventory questionnaire. The percentage of content validity from each students’ worksheets is 87,78%. Construct validity obtained a percentage from each students’ worksheets is 86,67%. The results of students' responses obtained an average percentage of 94,00% in the very practical category and was supported by the results of observations of students' activities by obtaining the percentage of relevant activities at meetings 1, 2, and 3 respectively 93.32%; 93.32%; and 96.65%. The results of students' metacognitive skills tests increased with a range of N-gain scores of 0.67 to 1.00 in the medium to high category. The knowledge domain test increased with a range of N-gain scores of 0.67 to 1.00 and was supported by the results of the metacognitive inventory questionnaire which obtained an average of 84.53 in the very good category. Based on the three aspects of the feasibility of the students’ worksheets above, it can be concluded that the problem solving oriented to train students' metacognitive skills in acid-base material is feasible to use.